Epitypification and update of biogeographical statut of Galactia nummularia (Fabaceae, Papilionoideae) - Ferlay, Benjamin; Andreis, Darlionei; Servientis, Nils (Phytotaxa, 2025)
Galactia nummularia was rediscovered in 2021 in Saint Martin after a long absence of contemporary records. Recent occurrences have also been reported in Anguilla and Saint Barthélemy. Initially described from an incomplete specimen, the species appears to exhibit marked morphological variability in its leaves in response to ecological conditions, making its identification challenging. These new observations, supported by specimen collections, have allowed for an update of both its description and biogeographical status.